What goes around comes around: How large are spillbacks from US monetary policy? - Max Breitenlechner; Georgios Georgiadis; Ben Schumann (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
We quantify spillbacks from US monetary policy based on structural scenario analysis and minimum relative entropy methods applied in a Bayesian proxy structural vector-autoregressive model for the time period from 1990 to 2019. We find that spillbacks account for up to half of the overall slowdown in domestic real activity in response to a contractionary US monetary policy shock. Moreover, spillbacks materialise as stock market wealth effects impinge on US consumption, and as Tobin's q effects impinge on US investment. In particular, a contractionary US monetary policy shock depresses global equity prices, weighing on the value of US households' portfolios; and it depresses earnings of US firms through declines in foreign sales inducing them to cut back investment. Net trade does not contribute to spillbacks because US monetary policy shocks affect exports and imports similarly. Finally, spillbacks materialise through advanced rather than through emerging market economies, consistent with their relative importance in US foreign equity holdings and US firms' foreign demand.
Keywords: F42; E52; C50; 330; US monetary policy; spillovers; spillbacks; Bayesian proxy structural VAR models